Developmental conditioning of endothelium-derived hyperpolarizing factor-mediated vasorelaxation - Stead, Rebecca (J Hypertens, 2016)
OBJECTIVES: The endothelium maintains vascular homeostasis through the release of endothelium-derived relaxing factors (EDRF) and endothelium-derived hyperpolarization (EDH). The balance in EDH : EDRF is disturbed in cardiovascular disease and may also be susceptible to developmental conditioning through exposure to an adverse uterine environment to predispose to later risk of hypertension and vascular disease. METHODS: Developmentally conditioned changes in EDH : EDRF signalling pathways were investigated in cremaster arterioles (18–32 μm diameter) and third-order mesenteric arteries of adult male mice offspring of dams fed either a fat-rich (high fat, HF, 45% energy from fat) or control (C, 10% energy from fat) diet. After weaning, offspring either continued on high fat or were placed on control diets to give four dietary groups (C/C, HF/C, C/HF, and HF/HF) and studied at 15 weeks of age. RESULTS: EDH via intermediate (IK(Ca)) and small (SK(ca)) conductance calcium-activated potassium channels contributed less than 10% to arteriolar acetylcholine-induced relaxation in in-situ conditioned HF/C offspring compared with ∼60% in C/C (P < 0.01). The conditioned reduction in EDH signalling in HF/C offspring was reversed in offspring exposed to a high-fat diet both before and after weaning (HF/HF, 55%, P < 0.01 vs. HF/C). EDH signalling was unaffected in arterioles from C/HF offspring. The changes in EDH : EDRF were associated with altered endothelial cell expression and localization of IK(Ca) channels. CONCLUSION: This is the first evidence that EDH-mediated microvascular relaxation is susceptible to an adverse developmental environment through down-regulation of the IK(Ca) signalling pathway. Conditioned offspring exposed to a ‘second hit’ (HF/HF) exhibit adaptive vascular mechanisms to preserve dilator function.